POTENSI KETERLIBATAN KELOMPOK SOSIAL DALAM PROGRAM SUPLEMENTASI TABLET TAMBAH DARAH PADA REMAJA PUTRI DESA SIRNAGALIH PADA MASA PANDEMI COVID-19 - Muhammad Reihan Arianda (2022)
Anemia still one of the global nutritional problems that have an impact on human health, and both social and economic development. According to WHO, the prevalence of anemia in adolescent girls in developing countries reaches 53.7%, caused by stress, menstruation, or late eating. Under WHO recommendations in 2011, efforts to overcome anemia in rheumatism and WUS are focused on promotion and prevention activities, one of which is supplementation of blood-added tablets. However, COVID-19 has had a primary impact on health services, namely supplementation that is ineffective and not even available to young women. The purpose of this study was to determine the potential involvement of social groups (coral cadets and cadres) in providing supplementation with blood-added tablets to young women in Sirnagalih Village, Jonggol District, Bogor Regency. The research method used is qualitative. The selection of informants in qualitative research was taken by purposive sampling, namely the selection of informants based on certain criteria. Balekambang Health Center cooperates with schools to distribute blood-added tablets. The COVID-19 pandemic has restricted young girls' access to iron tablets from school. Therefore, all informants (health center nutritionists, village heads, youth organizations, integrated healthcare center cadres, and youth) agreed to innovations involving social groups in terms of distribution and assistance for iron supplementation in Sirnagalih Village.